A novel compact 4 x 4 Multi-slot MIMO antenna for N78/79, Wi-Fi 5/6, and V2X/DSRC for 5G in Sub-6 GHz band - Pradeep, P.; Jaya Sankar, K.; Paidimarry, C. S. (Advanced electromagnetics, 2025)
In this article, a novel multi-slot 2-port and 4-port compact wideband MIMO antennas are designed for 5G communication in the sub-6 GHz band. The multi-slot antenna contains a rectangular patch with two square cuts at the lower corner of it. Here, two rectangular slots, one at the top edge and the other near the bottom edge of the antenna. The orthogonal placement technique helps to provide initial isolation between ports. Further, a P-shaped stub is added to the top edge of the antenna element to achieve very high isolation among 4 antennas. The FR4 substrate’s overall dimensions are considered 56 x 56 x 1.6 mm3. The proposed 4-port multi-slot antenna achieved isolation of > 15 dB in the operating frequency band from 3.60 GHz – 7.33 GHz. The 4-port multi-slot prototype results and its simulated results are almost similar. The radiation patterns in elevation and azimuth planes are stable, a peak gain and high efficiency are 5.2 dB and 95% respectively. This antenna performance can be envisaged for N78/79, Wi-Fi 5/6, and Vehicle2X/DSRC bands.